Negative electrode material for non-aqueous electrolyte secondary battery and non-aqueous electrolyte secondary battery

JP7620831B2Active Publication Date: 2025-01-24PANASONIC INTELLECTUAL PROPERTY MANAGEMENT CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2021536970
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-07-31
Filing Date
2020-07-21
Publication Date
2025-01-24
Estimated Expiration
2040-07-21

Smart Images

  • Figure 0007620831000002
    Figure 0007620831000002
  • Figure 0007620831000003
    Figure 0007620831000003
  • Figure 0007620831000001
    Figure 0007620831000001
Patent Text Reader

Abstract

A negative electrode material for nonaqueous electrolyte secondary batteries according to the present invention is provided with: a silicate phase; silicon particles dispersed in the silicate phase; and crystal phases dispersed in the silicate phase. The silicate phase contains at least one element E1 that is selected from the group consisting of alkali metal elements and group 2 elements. The crystal phases contain a rare earth element, silicon and oxygen.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention mainly relates to an improvement of a negative electrode of a non-aqueous electrolyte secondary battery.

Background Art

[0002] Non-aqueous electrolyte secondary batteries, particularly lithium-ion secondary batteries, are expected to be used as power sources for small consumer applications, power storage devices, and electric vehicles because they have a high voltage and a high energy density. As the energy density of batteries is required to be increased, the use of materials containing silicon (silicon), which alloy with lithium, as a negative electrode active material having a high theoretical capacity density is expected.

[0003] In Patent Document 1, in a non-aqueous electrolyte secondary battery, it has been proposed to use a negative electrode active material including a lithium silicate phase represented by Li 2z SiO 2+z (0 < z < 2) and silicon particles dispersed in the lithium silicate phase.

Prior Art Documents

Patent Documents

[0004]

Patent Document 1

Summary of the Invention

[0005] The negative electrode active material described in Patent Document 1 has a smaller irreversible capacity associated with charge and discharge than a composite (SiO 2 ) in which fine silicon is dispersed in the phase, and is advantageous for improving the initial charge and discharge efficiency. x )

[0006] However, with the improvement of the performance of portable electronic devices and the like, a further improvement in the initial charge and discharge efficiency is required.

[0007] In view of the above, one aspect of the present invention relates to a negative electrode material for a non-aqueous electrolyte secondary battery comprising: a silicate phase; silicon particles dispersed in the silicate phase; and a crystalline phase dispersed in the silicate phase, wherein the silicate phase contains at least one element E1 selected from the group consisting of alkali metal elements and Group 2 elements, and the crystalline phase contains a rare earth element, silicon, and oxygen.

[0008] Another aspect of the present invention relates to a non-aqueous electrolyte secondary battery comprising a positive electrode, a negative electrode, and a non-aqueous electrolyte, the negative electrode containing the above-mentioned negative electrode material for non-aqueous electrolyte secondary batteries.

[0009] According to the present invention, the initial charge / discharge efficiency of a nonaqueous electrolyte secondary battery can be improved. [Brief description of the drawings]

[0010] [Figure 1] FIG. 1 is a schematic diagram showing a cross section of a negative electrode material according to one embodiment of the present invention. [Diagram 2] 1 is a schematic perspective view of a nonaqueous electrolyte secondary battery according to one embodiment of the present invention, with a portion cut away; DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] [Non-aqueous electrolyte secondary battery negative electrode material] The negative electrode material for a non-aqueous electrolyte secondary battery according to an embodiment of the present invention (hereinafter, also referred to as a composite material) comprises a silicate phase (also simply referred to as a silicate phase) containing an element E1, and silicon particles dispersed in the silicate phase. The element E1 is at least one element selected from the group consisting of an alkali metal element and a Group 2 element. A crystalline phase (also simply referred to as a crystalline phase) containing a rare earth element, silicon (Si), and oxygen (O) is further dispersed in the silicate phase.

[0012] By dispersing a crystalline phase that is less reactive with lithium ions in a matrix of a silicate phase, the number of sites that can react with lithium ions in the silicate phase is reduced, the irreversible capacity is reduced, and the initial charge / discharge efficiency is improved. In order to disperse the crystalline phase in the matrix of the silicate phase, the crystalline phase may be generated in the silicate phase during the manufacturing process of the negative electrode material. In this case, the number of sites that can react with lithium ions can be reduced more efficiently.

[0013] When a crystalline phase containing a rare earth element, silicon, and oxygen is dispersed in a matrix of a silicate phase containing element E1, the initial charge-discharge efficiency is significantly improved. Although the detailed reason is not clear, it is speculated that the crystalline phase containing a rare earth element, silicon, and oxygen has a particularly low reactivity with lithium ions and is difficult to absorb lithium ions, so that side reactions can be significantly reduced in the early stages of charge-discharge, and the initial charge-discharge efficiency is significantly improved.

[0014] The crystalline phase is formed by highly crystalline rare earth silicate. When the crystallinity of the rare earth silicate is high, a diffraction peak with a half-width of 0.75° or less is observed at a diffraction angle of 2θ=33° in the X-ray diffraction pattern of the composite material obtained by X-ray diffraction measurement using Cu-Kα radiation.

[0015] The higher the crystallinity of the rare earth silicate, the more desirable it is. In this case, the reactivity of the crystalline phase with ions such as lithium ions is further reduced, and the lithium ion conductivity is improved, which reduces the resistance during discharge and tends to improve the initial charge / discharge efficiency.

[0016] In this specification, the half width means the full width at half maximum (FWHM). In addition, in this specification, with respect to the position where the diffraction peak is observed, "near D°" means within the range of more than D-0.5° and less than D+0.5°.

[0017] In the composite material, the content of the rare earth element is preferably 0.2 mass% or more and 21 mass% or less, more preferably 2.4 mass% or more and 15 mass% or less, and even more preferably 5.5 mass% or more and 14 mass% or less, based on the total amount of elements other than oxygen. When the content of the rare earth element in the composite material is 0.2 mass% or more based on the total amount of elements other than oxygen, the effect of improving the initial charge and discharge efficiency is easily obtained. When the content of the rare earth element in the composite material is 21 mass% or less based on the total amount of elements other than oxygen, the silicate phase of element E1 is easily secured in the composite material. When the silicate phase of element E1 with low crystallinity is sufficiently present in the composite material, the lithium ion conductivity is easily improved in the composite material, and the stress caused by the expansion and contraction of silicon particles is easily alleviated.

[0018] The content of the rare earth element in the composite material can be determined, for example, by the following method.

[0019] The battery is disassembled, the negative electrode is removed, washed with a non-aqueous solvent such as ethylene carbonate, dried, and then the cross section of the negative electrode mixture layer is processed using a cross section polisher (CP) to obtain a sample. A field emission scanning electron microscope (FE-SEM) is used to obtain a backscattered electron image of the sample cross section, and the cross section of the composite material particle is observed. An Auger electron spectroscopy (AES) analyzer (JEOL, JAMP-9510F) is used to perform qualitative and quantitative analysis of elements in a certain area in the center of the cross section of the observed composite material particle (accelerating voltage 10 kV, beam current 10 nA, analysis area 20 μmφ). Based on the results of the above analysis, the content of rare earth elements in the composite material particle (the mass ratio of rare earth elements to the total mass of elements other than oxygen contained in the composite material particle) is obtained. An analysis is performed on the 10 observed composite material particles, and the average content of rare earth elements is obtained.

[0020] The rare earth element preferably contains at least one selected from the group consisting of lanthanum (La), cerium (Ce), praseodymium (Pr) and neodymium (Nd). From the viewpoint of improving lithium ion conductivity, the rare earth element more preferably contains La. The proportion of La in the total rare earth elements is preferably 90 atomic % or more and 100 atomic % or less.

[0021] The crystalline phase may be, for example, a compound represented by the general formula: M 2 O 3 ·ySiO 2 The formula: y is, for example, 1.0 to 2.0. M is a rare earth element. The crystal phase has a high structural stability and is not easily dissolved in an electrolyte, and is therefore preferably a compound represented by the general formula: M 2 S 2 O 7 (M is a rare earth element). Among them, La 2 S 2 O 7 More preferably, the crystal phase is M 2 S 2 O 7 When the compound A represented by (M is a rare earth element) is contained, the crystal structure of the crystal phase contains at least one type selected from the group consisting of monoclinic, tetragonal and triclinic crystals.

[0022] The fact that the crystalline phase containing the rare earth element, silicon, and oxygen is dispersed in the matrix of the silicate phase of element E1 can be confirmed by observing a cross-sectional image (backscattered electron image) of the composite material obtained using a scanning electron microscope (SEM) or a transmission electron microscope (TEM). The equivalent circle diameter of the crystalline phase dispersed in the silicate phase is, for example, 10 nm or more and 1 μm or less. The equivalent circle diameter of the crystalline phase is determined using a cross-sectional image (backscattered electron image) of the composite material obtained by SEM or TEM. Specifically, the area of ​​100 crystalline phases is converted into the diameter of an equivalent circle and averaged to determine the equivalent circle diameter.

[0023] The crystal phase containing rare earth elements, silicon, and oxygen can be confirmed by X-ray diffraction measurement using Cu-Kα radiation. For example, when the crystal phase of compound A is dispersed in the silicate phase, diffraction peaks attributable to compound A are observed at diffraction angles 2θ=26°, 27°, 28°, and 33° in the X-ray diffraction pattern of the composite material.

[0024] The crystal phase containing the rare earth element, silicon, and oxygen may be confirmed by electron beam diffraction measurement using a field emission transmission electron microscope (manufactured by JEOL Ltd., JEM2100F, accelerating voltage 200 kV, accelerating current 110 μA). Based on the data of the diffraction point (distance from the center point) obtained by the electron beam diffraction measurement, the interplanar spacing and crystal structure attributed to compound A can be obtained. Based on the obtained interplanar spacing and crystal structure and the elements contained in the crystal phase obtained by energy dispersive X-ray analysis (EDX), the composition of the crystal phase can be identified.

[0025] In addition, when silicon particles and a crystalline phase of compound A are dispersed in the silicate phase, the first diffraction peak attributed to compound A and the second diffraction peak attributed to silicon particles are observed near the diffraction angles 2θ = 33° and 29°, respectively, in the X-ray diffraction pattern of the composite material. The second diffraction peak is the diffraction peak of the (111) plane of Si.

[0026] The ratio I1 / I2 of the intensity I1 of the first diffraction peak to the intensity I2 of the second diffraction peak is preferably 0.25 or less. In this case, silicon particles and the crystalline phase of compound A are dispersed in a well-balanced manner in the silicate phase, which makes it easy to increase the capacity of the negative electrode and to improve the initial charge / discharge efficiency.

[0027] The diffraction peaks attributed to compound A depend on the crystal structure of compound A, and in the case of a monoclinic crystal, they include the diffraction peaks of the (20-2), (122), (113), (03-2) or (11-5) planes. In the case of a tetragonal crystal, they include the diffraction peaks of the (124) or (026) planes. In the case of a triclinic crystal, they include the diffraction peak of the (203) plane.

[0028] The crystalline phase of compound A has interplanar spacings of at least 2.6 Å to 2.75 Å, 3.6 Å to 3.7 Å, 5.2 Å to 5.3 Å, and 7.3 Å to 7.4 Å.

[0029] The composite material will be described in detail below.

[0030] The silicate phase containing element E1 is SiO x SiO 2 Compared to the SiO phase, the composite has fewer sites that can react with lithium. x Compared to the conventional lithium-ion battery, it is less likely to experience irreversible capacity during charging and discharging, and has a high initial charge-discharge efficiency. In addition, the content of silicon particles can be freely changed, making it possible to design a high-capacity anode.

[0031] The silicate phase of element E1 can form an amorphous or near-amorphous phase by the method for producing the negative electrode material described later. From the viewpoints of improving the lithium ion conductivity of the composite particles, relaxing the stress caused by the expansion and contraction of silicon particles during charging and discharging, and suppressing particle cracking of the composite material, it is preferable that the crystallinity of the matrix of the silicate phase is low. In the X-ray diffraction pattern of the composite material obtained by X-ray diffraction measurement using Cu-Kα radiation, the half-width of the diffraction peak of the (111) plane of the silicate of element E1 is, for example, 0.05° or more, and may be 0.5° or more.

[0032] The silicate phase includes a silicate of element E1. Element E1 includes at least one of an alkali metal element (a Group 1 element other than hydrogen in the long periodic table) and a Group 2 element in the long periodic table. Alkali metal elements include lithium (Li), potassium (K), sodium (Na), etc. Group 2 elements include magnesium (Mg), calcium (Ca), barium (Ba), etc. Element E1 may be used alone or in combination of two or more.

[0033] The silicate phase may further contain element E2. Element E2 can include zirconium (Zr), niobium (Nb), tantalum (Ta), vanadium (V), titanium (Ti), phosphorus (P), bismuth (Bi), zinc (Zn), tin (Sn), lead (Pb), antimony (Sb), cobalt (Co), fluorine (F), tungsten (W), aluminum (Al), boron (B), etc. Element E2 may be used alone or in combination of two or more. When the silicate phase contains element E2, the chemical stability, lithium ion conductivity, etc. of the composite material are improved. Side reactions due to the contact between the silicate phase and the non-aqueous electrolyte are suppressed. From the viewpoints of electrolyte resistance and structural stability, element E2 is preferably at least one selected from the group consisting of Zr, Ti, P, Al, and B. Element E2 may form a compound. The compound may be, for example, a silicate of element E2 or an oxide of element E2 depending on the type of element E2.

[0034] Also, the silicate phase may further contain trace amounts of other elements such as iron (Fe), chromium (Cr), nickel (Ni), manganese (Mn), copper (Cu), molybdenum (Mo), etc.

[0035] The silicate phase includes, for example, a lithium silicate phase containing lithium (Li), silicon (Si), and oxygen (O). The atomic ratio of O to Si in the lithium silicate phase: O / Si is, for example, greater than 2 and less than 4. When O / Si is greater than 2 and less than 4 (z is 0 < z < 2 in the formula described later), it is advantageous in terms of stability and lithium ion conductivity. Preferably, O / Si is greater than 2 and less than 3 (z is 0 < z < 1 in the formula described later). The atomic ratio of Li to Si in the lithium silicate phase: Li / Si is, for example, greater than 0 and less than 4.

[0036] The lithium silicate phase may have a composition represented by the formula: Li 2z SiO 2+z (0 < z < 2). From the viewpoints of stability, ease of production, lithium ion conductivity, etc., z preferably satisfies the relationship of 0 < z < 1, and z = 1 / 2 is more preferable.

[0037] The composition of the silicate phase of the composite material can be analyzed, for example, by the following method.

[0038] The battery is disassembled, the negative electrode is removed, washed with a non-aqueous solvent such as ethylene carbonate, dried, and then the cross section of the negative electrode mixture layer is processed using a cross section polisher (CP) to obtain a sample. A field emission scanning electron microscope (FE-SEM) is used to obtain a backscattered electron image of the sample cross section, and the cross section of the composite material particle is observed. An Auger electron spectroscopy (AES) analyzer (JAMP-9510F, manufactured by JEOL Ltd.) is used to perform qualitative and quantitative elemental analysis of the silicate phase of the observed composite material particle (accelerating voltage 10 kV, beam current 10 nA, analysis area 20 μmφ). For example, the composition of the silicate phase is determined based on the obtained content of element E1 (Li, etc.), silicon (Si), oxygen (O), and other elements. In addition, the quantitative determination of each element in the composite material in a discharged state can be performed using energy dispersive X-ray analysis (EDX), electron microanalyzer (EPMA), laser ablation inductively coupled plasma mass spectrometry (LA-ICP-MS), X-ray photoelectron spectroscopy (XPS), etc.

[0039] In the cross-sectional observation and analysis of the above samples, a carbon sample stage can be used to fix the sample in place to prevent diffusion of Li. A transfer vessel can be used to hold and transport the sample without exposing it to the atmosphere to prevent deterioration of the sample cross section.

[0040] The silicon particles dispersed in the silicate phase have a particulate phase of silicon (Si) alone, and are usually composed of multiple crystallites. The crystallite size of the silicon particles is preferably 30 nm or less. When the crystallite size of the silicon particles is 30 nm or less, the volume change due to the expansion and contraction of the silicon particles accompanying charging and discharging can be reduced, and the cycle characteristics can be further improved. For example, when the silicon particles contract, voids are formed around the silicon particles, reducing the contact points with the surroundings of the particles, suppressing the isolation of the particles, and suppressing the decrease in charge and discharge efficiency due to the isolation of the particles. The lower limit of the crystallite size of the silicon particles is not particularly limited, but the crystallite size of the silicon particles is, for example, 1 nm or more.

[0041] The crystallite size of the silicon particles is more preferably 10 nm or more and 30 nm or less, and further preferably 15 nm or more and 25 nm or less. When the crystallite size of the silicon particles is 10 nm or more, the surface area of ​​the silicon particles can be kept small, so that the deterioration of the silicon particles accompanied by the generation of irreversible capacity is unlikely to occur.

[0042] The crystallite size of silicon particles is calculated from the half-width of the diffraction peak attributable to the (111) plane of the silicon particle (simple Si) in the X-ray diffraction pattern by Scherrer's formula.

[0043] The composite material also has excellent structural stability. Since the silicon particles are dispersed in the silicate phase, the expansion and contraction of the composite material accompanying charging and discharging is suppressed. From the viewpoint of suppressing cracks in the silicon particles themselves, the average particle size of the silicon particles is preferably 500 nm or less, more preferably 200 nm or less, and even more preferably 50 nm or less, before the first charge. After the first charge, the average particle size of the silicon particles is preferably 400 nm or less, more preferably 100 nm or less. By making the silicon particles finer, the volume change during charging and discharging is reduced, and the structural stability of the composite material is further improved.

[0044] The average particle size of silicon particles is measured using a cross-sectional image of the composite material obtained by SEM. Specifically, the average particle size of silicon particles is calculated by averaging the maximum diameters of 100 random silicon particles.

[0045] From the viewpoint of increasing the capacity, the content of silicon particles in the composite material is preferably 30% by mass or more, more preferably 35% by mass or more, and even more preferably 55% by mass or more. In this case, the diffusibility of lithium ions is good, and excellent load characteristics are easily obtained. On the other hand, from the viewpoint of improving cycle characteristics, the content of silicon particles in the composite material is preferably 95% by mass or less, more preferably 75% by mass or less, and even more preferably 70% by mass or less. In this case, the surface of the silicon particles that is exposed without being covered with the silicate phase is reduced, and the reaction between the nonaqueous electrolyte and the silicon particles is easily suppressed.

[0046] The composite material is preferably particulate. The average particle size of the composite material particles is, for example, 1 μm or more and 25 μm or less, and may be 4 μm or more and 15 μm or less. In the above particle size range, it is easy to relieve stress caused by volumetric changes in the composite material during charging and discharging, and good cycle characteristics are easily obtained. The surface area of ​​the composite material particles is also appropriate, and capacity loss due to side reactions with the non-aqueous electrolyte is also suppressed.

[0047] The average particle size of the composite material particles means the particle size (volume average particle size) at which the volume cumulative value is 50% in the particle size distribution measured by the laser diffraction scattering method. For example, the "LA-750" manufactured by HORIBA Co., Ltd. can be used as the measuring device.

[0048] At least a part of the surface of the composite material may be covered with a conductive layer. This enhances the electrical conductivity of the composite material. The conductive layer is preferably thin enough that it does not substantially affect the average particle size of the composite material particles. In consideration of ensuring electrical conductivity and diffusibility of lithium ions, the thickness of the conductive layer is preferably 1 nm or more and 200 nm or less, more preferably 5 nm or more and 100 nm or less. The thickness of the conductive layer can be measured by observing the cross section of the composite material using a SEM or TEM.

[0049] [Method of producing negative electrode material] A method for producing a negative electrode material includes, for example, a first step of obtaining a raw silicate containing element E1 and a rare earth element, a second step of combining the raw silicate with raw silicon to obtain a composite intermediate in which silicon particles and silicate containing a rare earth element are dispersed in a silicate phase containing element E1, and a third step of subjecting the composite intermediate to a heat treatment to increase the crystallinity of the silicate containing rare earth element, thereby obtaining a composite material in which a crystalline phase of silicon particles and silicate containing a rare earth element is dispersed in a silicate phase containing element E1.

[0050] [1st step] The first step includes, for example, step 1a of mixing silicon dioxide, a compound containing element E1, and a compound containing a rare earth element to obtain a mixture, and step 1b of firing the mixture to obtain a raw silicate containing element E1 and a rare earth element. The firing in step 1b is performed, for example, in an oxidizing atmosphere. The firing temperature in step 1b is preferably 400° C. or higher and 1200° C. or lower, more preferably 800° C. or higher and 1100° C. or lower. In the first step, a silicate containing element E1 and a silicate containing a rare earth element may be obtained separately as the raw silicate.

[0051] Examples of the compound containing element E1 include carbonates, oxides, hydroxides, hydrides, etc. of element E1. For example, examples of the lithium compound include lithium carbonate, lithium oxide, lithium hydroxide, lithium hydride, etc. The compound containing element E1 may be used alone or in combination of two or more.

[0052] Examples of the compound containing a rare earth element include oxides, oxalates, nitrates, sulfates, halides, and carbonates of rare earth elements. For example, an example of a lanthanum compound is lanthanum oxide. The compound containing a rare earth element may be used alone or in combination of two or more kinds.

[0053] [Second process] In the second step, a composite intermediate is obtained that includes a silicate phase containing element E1, silicon particles dispersed in the silicate phase, and a silicate of a rare earth element dispersed in the silicate phase. By appropriately adjusting the compounding ratio of the compound containing element E1 and the compound containing a rare earth element in the first step, the silicate of the rare earth element can be dispersed together with the silicon particles in the matrix of the silicate containing element E1 in the composite intermediate. In the second step, a silicate containing element E1 and a silicate of a rare earth element that are low in crystallinity can be formed in the composite intermediate.

[0054] In the second step, the silicate containing element E1 and a rare earth element may be composited with the raw material silicon, or the silicate containing element E1, the silicate containing a rare earth element, and the raw material silicon may be composited.

[0055] The raw silicon may be coarse silicon particles having an average particle size of several μm to several tens of μm. The silicon particles finally obtained are preferably controlled so that the crystallite size calculated from the half-width of the diffraction peak assigned to the Si(111) plane in the X-ray diffraction pattern by the Scherrer formula is 10 nm or more.

[0056] The second step includes, for example, a step 2a of pulverizing the mixture of raw silicate and raw silicon while applying a shear force to the mixture to obtain a finely divided mixture, and a step 2b of sintering the finely divided mixture to obtain a composite intermediate. In the composite intermediate thus obtained, the silicate of element E1 and the silicate of rare earth elements have low crystallinity.

[0057] In step 2a, for example, raw silicate and raw silicon are mixed in a predetermined mass ratio, and the mixture is stirred while being finely divided using a grinding device such as a ball mill. However, step 2a is not limited to this. For example, silicon nanoparticles and raw silicate nanoparticles may be synthesized and mixed without using a grinding device.

[0058] In step 2b, the mixture may be sintered while applying pressure using a hot press or the like to produce a sintered body (composite intermediate) of the mixture. The sintered body may then be pulverized into granular matter to produce particles of the composite intermediate. At this time, by appropriately selecting the pulverization conditions, composite intermediate particles having an average particle size of, for example, 1 to 25 μm can be obtained.

[0059] The firing in step 2b is carried out, for example, in an inert atmosphere (for example, an atmosphere of argon, nitrogen, etc.). The firing temperature in step 2b is preferably 450°C or higher and 1000°C or lower. In the above temperature range, it is easy to disperse fine silicon particles in the silicate phase with low crystallinity. In addition, the raw silicate is stable in the above temperature range and hardly reacts with silicon, so that even if a capacity reduction occurs, it is minor.

[0060] In the first or second step, a compound containing element E2 may be further added. Examples of the compound containing element E2 include oxides, oxalates, nitrates, sulfates, halides, carbonates, etc. of element E2. Among them, oxides are preferred because they are stable and have good ion conductivity. The compound containing element E2 may be used alone or in combination of two or more.

[0061] [3rd step] In the third step, the composite intermediate is subjected to a predetermined heat treatment. At this time, the crystallinity of the silicate of the rare earth element dispersed in the silicate phase is improved, and a crystalline phase of the silicate of the rare earth element is formed. Since the rare earth element cuts the silicate framework and forms an ionic bond, the heat treatment easily turns it into a stable crystalline rare earth silicate.

[0062] The heat treatment temperature is preferably 550°C or more and 900°C or less, more preferably 650°C or more and 850°C or less. When the heat treatment temperature is 550°C or more, a crystal phase of silicate of rare earth element is easily formed. When the heat treatment temperature is 900°C or less, the crystallinity of the silicate phase of element E1 is easily maintained in a low state, and the silicon particles dispersed in the silicate phase are easily maintained in a small size. The heat treatment time is, for example, 1 hour or more and 10 hours or less. The heat treatment may be performed in an oxidizing atmosphere or an inert atmosphere.

[0063] [4th step] The method for producing the negative electrode material may further include a fourth step of forming a conductive layer containing a conductive material on at least a part of the surface of the composite material. The conductive material is preferably electrochemically stable, and is preferably a carbon material. For example, a method of forming a conductive layer on the surface of the composite material may include a method of mixing coal pitch, petroleum pitch, phenolic resin, etc. with composite material particles and heating to carbonize the mixture. The heating for the purpose of carbonization may also serve as the heat treatment in the third step. Alternatively, a conductive layer containing a carbon material may be formed on the surface of the composite material particles by a CVD method using a hydrocarbon gas such as acetylene or methane as a raw material. Carbon black may be attached to the surface of the composite material particles.

[0064] [5th ​​step] The method for producing a negative electrode material may further include a fifth step of washing the composite material with an acid. For example, by washing the composite material containing lithium silicate with an acidic aqueous solution, trace amounts of Li that may be generated when the raw silicon and lithium silicate are combined can be removed. 2 SiO 3 As the acidic aqueous solution, an aqueous solution of an inorganic acid such as hydrochloric acid, hydrofluoric acid, sulfuric acid, nitric acid, phosphoric acid, or carbonic acid, or an aqueous solution of an organic acid such as citric acid or acetic acid can be used.

[0065] An example of a negative electrode material for a non-aqueous electrolyte secondary battery according to one embodiment of the present invention will now be described with reference to Fig. 1. Fig. 1 is a schematic diagram showing a cross section of a negative electrode material (composite material 11).

[0066] The composite material 11 is particulate and includes a silicate phase 12 of element E1, silicon (simple Si) particles 13 dispersed in the silicate phase 12, and a crystal phase 14 of a silicate of a rare earth element dispersed in the silicate phase 12. As shown in Fig. 1, at least a portion of the surface of the particulate composite material 11 may be covered with a conductive layer 15 containing a conductive material.

[0067] The composite material 11 has, for example, an island-in-a-sea structure, and in any cross section, fine silicon particles 13 and crystalline phases 14 are scattered approximately uniformly, without being unevenly distributed in some regions, in a matrix of a silicate phase 12. Most of the crystalline phases 14 are larger in size than the silicon particles 13.

[0068] The silicate phase 12 is preferably composed of particles finer than the silicon particles 13. In this case, in the X-ray diffraction pattern of the negative electrode material, the intensity of the diffraction peak attributable to the (111) plane of simple substance Si is greater than the intensity of the diffraction peak attributable to the (111) plane of the silicate of element E1.

[0069] The silicate phase 12 may further contain element E2. The silicate phase 12 may also contain SiO2, which is about the same as a natural oxide film formed on the surface of silicon particles. 2 may include:

[0070] [Nonaqueous electrolyte secondary battery] A non-aqueous electrolyte secondary battery according to an embodiment of the present invention includes a positive electrode, a negative electrode, and a non-aqueous electrolyte, and the negative electrode contains the above-mentioned negative electrode material for non-aqueous electrolyte secondary batteries.

[0071] The nonaqueous electrolyte secondary battery will be described in detail below.

[0072] [Negative electrode] The negative electrode may include a negative electrode current collector and a negative electrode mixture layer supported on the surface of the negative electrode current collector. The negative electrode mixture layer can be formed by applying a negative electrode slurry, in which the negative electrode mixture is dispersed in a dispersion medium, to the surface of the negative electrode current collector and drying the applied film. The coating film after drying may be rolled as necessary. The negative electrode mixture layer may be formed on one surface or both surfaces of the negative electrode current collector.

[0073] The negative electrode mixture contains a negative electrode active material as an essential component, and may contain, as optional components, a binder, a conductive agent, a thickener, etc. For the negative electrode active material, the above-mentioned negative electrode material (composite material) is used.

[0074] The negative electrode active material preferably further contains a carbon material that electrochemically absorbs and releases lithium ions. Since the composite material expands and contracts in volume with charging and discharging, when the ratio of the composite material in the negative electrode active material increases, poor contact between the negative electrode active material and the negative electrode current collector is likely to occur with charging and discharging. On the other hand, by using the composite material and the carbon material in combination, it is possible to achieve excellent cycle characteristics while imparting high capacity of silicon particles to the negative electrode. From the viewpoint of increasing capacity and improving cycle characteristics, the ratio of the carbon material to the total of the silicon-containing material and the carbon material is preferably 98 mass% or less, more preferably 70 mass% or more and 98 mass% or less, and even more preferably 75 mass% or more and 95 mass% or less.

[0075] Examples of carbon materials include graphite, graphitizable carbon (soft carbon), and non-graphitizable carbon (hard carbon). Among them, graphite is preferable because it has excellent charge / discharge stability and low irreversible capacity. Graphite means a material having a graphite type crystal structure, and includes, for example, natural graphite, artificial graphite, graphitized mesophase carbon particles, and the like. The carbon material may be used alone or in combination of two or more kinds.

[0076] As the negative electrode current collector, a non-porous conductive substrate (metal foil, etc.) or a porous conductive substrate (mesh, net, punched sheet, etc.) is used. Examples of the material of the negative electrode current collector include stainless steel, nickel, nickel alloy, copper, copper alloy, etc. The thickness of the negative electrode current collector is not particularly limited, but is preferably 1 to 50 μm, more preferably 5 to 20 μm, from the viewpoint of the balance between the strength and weight reduction of the negative electrode.

[0077] Examples of the binder include resin materials, such as fluororesins such as polytetrafluoroethylene and polyvinylidene fluoride (PVDF); polyolefin resins such as polyethylene and polypropylene; polyamide resins such as aramid resin; polyimide and polyamideimide; acrylic resins such as polyacrylic acid, polymethyl acrylate, and ethylene-acrylic acid copolymer; vinyl resins such as polyacrylonitrile and polyvinyl acetate; polyvinylpyrrolidone; polyethersulfone; and rubber-like materials such as styrene-butadiene copolymer rubber (SBR). One type of binder may be used alone, or two or more types may be used in combination.

[0078] Examples of the conductive agent include carbons such as acetylene black, conductive fibers such as carbon fibers and metal fibers, carbon fluoride, metal powders such as aluminum, conductive whiskers such as zinc oxide and potassium titanate, conductive metal oxides such as titanium oxide, and organic conductive materials such as phenylene derivatives. The conductive agent may be used alone or in combination of two or more.

[0079] Examples of thickeners include carboxymethylcellulose (CMC) and its modified products (including salts such as Na salt), cellulose derivatives such as methylcellulose (cellulose ethers, etc.), saponified polymers having vinyl acetate units such as polyvinyl alcohol, polyethers (polyalkylene oxides such as polyethylene oxide, etc.), etc. One type of thickener may be used alone, or two or more types may be used in combination.

[0080] The dispersion medium is not particularly limited, but examples thereof include water, alcohols such as ethanol, ethers such as tetrahydrofuran, amides such as dimethylformamide, N-methyl-2-pyrrolidone (NMP), and mixed solvents thereof.

[0081] [Positive electrode] The positive electrode may include a positive electrode current collector and a positive electrode mixture layer supported on the surface of the positive electrode current collector. The positive electrode mixture layer can be formed by applying a positive electrode slurry in which the positive electrode mixture is dispersed in a dispersion medium to the surface of the positive electrode current collector and drying it. The coating film after drying may be rolled as necessary. The positive electrode mixture layer may be formed on one surface of the positive electrode current collector or on both surfaces. The positive electrode mixture includes a positive electrode active material as an essential component, and may include a binder, a conductive agent, etc. as optional components. NMP or the like is used as the dispersion medium of the positive electrode slurry.

[0082] As the positive electrode active material, for example, a lithium-containing composite oxide can be used. a Chief of Staff 2 , Li a NiO 2 , Li a MnO 2 , Li a Co b Ni 1-b O 2 , Li a Co b Me 1-b O c , Li a Ni 1-b Me b O c , Li a Mn 2 O 4 , Li a Mn 2-b Me b O 4、 LiMePO 4、 Li 2 MePO 4F (Me is at least one selected from the group consisting of Na, Mg, Sc, Y, Mn, Fe, Co, Ni, Cu, Zn, Al, Cr, Pb, Sb, and B). Here, a = 0 to 1.2, b = 0 to 0.9, and c = 2.0 to 2.3. Note that the a value indicating the molar ratio of lithium increases or decreases upon charge and discharge.) is exemplified.

[0083] Among them, Li a Ni b Me 1-b O 2 (Me is at least one selected from the group consisting of Mn, Co, and Al, 0 < a ≤ 1.2, and 0.3 ≤ b ≤ 1.) The lithium nickel composite oxide represented by is preferable. From the viewpoint of increasing the capacity, it is more preferable to satisfy 0.85 ≤ b ≤ 1. From the viewpoint of the stability of the crystal structure, Li containing Co and Al as Me a Ni b Co c Al d O 2 (0 < a ≤ 1.2, 0.85 ≤ b < 1, 0 < c < 0.15, 0 < d ≤ 0.1, b + c + d = 1) is even more preferable.

[0084] As the binder and the conductive agent, the same ones as those exemplified for the negative electrode can be used. As the conductive agent, graphite such as natural graphite and artificial graphite may be used.

[0085] The shape and thickness of the positive electrode current collector can be selected from the shapes and ranges according to the negative electrode current collector. Examples of the material of the positive electrode current collector include stainless steel, aluminum, aluminum alloy, titanium, and the like.

[0086] [Non-aqueous electrolyte] The non-aqueous electrolyte includes a non-aqueous solvent and a lithium salt dissolved in the non-aqueous solvent. The concentration of the lithium salt in the non-aqueous electrolyte is preferably, for example, 0.5 mol / L or more and 2 mol / L or less. By setting the lithium salt concentration within the above range, a non-aqueous electrolyte having excellent ionic conductivity and appropriate viscosity can be obtained. However, the lithium salt concentration is not limited to the above.

[0087] Examples of the non-aqueous solvent include cyclic carbonates, chain carbonates, cyclic carboxylates, and chain carboxylates. Examples of the cyclic carbonates include propylene carbonate (PC) and ethylene carbonate (EC). Examples of the chain carbonates include diethyl carbonate (DEC), ethyl methyl carbonate (EMC), and dimethyl carbonate (DMC). Examples of the cyclic carboxylates include γ-butyrolactone (GBL) and γ-valerolactone (GVL). Examples of the chain carboxylates include methyl formate, ethyl formate, propyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, and propyl propionate. The non-aqueous solvent may be used alone or in combination of two or more.

[0088] The lithium salt is, for example, LiClO 4 , LiBF 4 , LiPF 6 , LiAlCl 4 , LiSbF 6 , LiSCN, LiCF 3 SO 3 , LiCF 3 CO 2 , LiAsF 6 , LiB 10 Cl 10 , lithium aliphatic carboxylates, LiCl, LiBr, LiI, borates, imide salts, etc. Examples of borates include lithium bis(1,2-benzenedioleate(2-)-O,O')borate, lithium bis(2,3-naphthalenediolate(2-)-O,O')borate, lithium bis(2,2'-biphenyldioleate(2-)-O,O')borate, lithium bis(5-fluoro-2-oleate-1-benzenesulfonic acid-O,O')borate, etc. Examples of imide salts include lithium bisfluorosulfonylimide (LiN(FSO 2 ) 2 ), lithium bistrifluoromethanesulfonimide (LiN(CF 3 SO 2 ) 2), lithium trifluoromethanesulfonate nonafluorobutanesulfonimide (LiN(CF 3 SO 2 )(C 4 F 9 SO 2 )), lithium bispentafluoroethanesulfonimide (LiN(C 2 F 5 SO 2 ) 2 Among these, LiPF 6 LiPF is preferred. 6 Lithium salts are prone to form passive films on the surfaces of battery components such as positive electrode current collectors. The passive films can protect the above components. The lithium salts may be used alone or in combination of two or more.

[0089] [Separator] Usually, it is desirable to interpose a separator between the positive electrode and the negative electrode. The separator has high ion permeability and has appropriate mechanical strength and insulation properties. As the separator, a microporous thin film, a woven fabric, a nonwoven fabric, etc. can be used. As the material of the separator, polyolefin such as polypropylene and polyethylene is preferable.

[0090] An example of the structure of the non-aqueous electrolyte secondary battery is a structure in which an electrode group formed by winding a positive electrode and a negative electrode with a separator interposed therebetween and a non-aqueous electrolyte are housed in an exterior body. Alternatively, instead of a wound type electrode group, an electrode group of another form, such as a stacked type electrode group formed by stacking a positive electrode and a negative electrode with a separator interposed therebetween, may be applied. The non-aqueous electrolyte secondary battery may be in any form, such as a cylindrical type, a square type, a coin type, a button type, a laminate type, or the like.

[0091] Hereinafter, as one example of the nonaqueous electrolyte secondary battery according to the present invention, the structure of a prismatic nonaqueous electrolyte secondary battery will be described with reference to Fig. 2. Fig. 2 is a schematic perspective view of a nonaqueous electrolyte secondary battery according to one embodiment of the present invention, with a portion cut away.

[0092] The battery includes a bottomed prismatic battery case 4, and an electrode group 1 and a non-aqueous electrolyte (not shown) housed within the battery case 4. The electrode group 1 includes a long strip-shaped negative electrode, a long strip-shaped positive electrode, and a separator interposed between them to prevent direct contact. The electrode group 1 is formed by winding the negative electrode, positive electrode, and separator around a flat plate-shaped winding core and then removing the winding core.

[0093] One end of the negative electrode lead 3 is attached to the negative electrode current collector of the negative electrode by welding or the like. The other end of the negative electrode lead 3 is electrically connected to a negative electrode terminal 6 provided on the sealing plate 5 via a resin insulating plate (not shown). The negative electrode terminal 6 is insulated from the sealing plate 5 by a resin gasket 7. One end of the positive electrode lead 2 is attached to the positive electrode current collector of the positive electrode by welding or the like. The other end of the positive electrode lead 2 is connected to the back surface of the sealing plate 5 via an insulating plate. That is, the positive electrode lead 2 is electrically connected to the battery case 4 which also serves as the positive electrode terminal. The insulating plate separates the electrode group 1 and the sealing plate 5, and separates the negative electrode lead 3 and the battery case 4. The periphery of the sealing plate 5 is fitted into the open end of the battery case 4, and the fitting portion is laser welded. In this way, the opening of the battery case 4 is sealed with the sealing plate 5. The injection hole for the non-aqueous electrolyte provided in the sealing plate 5 is closed with a sealing plug 8 .

[0094] The present invention will be specifically described below based on examples and comparative examples, but the present invention is not limited to the following examples.

[0095] <Examples 1 to 4 and Comparative Examples 1 to 5> [Preparation of negative electrode material] [1st step] Silicon dioxide and a compound containing element X were mixed, and the mixture was fired in air at 950°C for 10 hours. In this way, a silicate containing element X was obtained. The obtained silicate was pulverized to an average particle size of 10 μm.

[0096] The elements shown in Table 1 were used as element X. When element X was Li, Na, or K, the compounds containing element X included Li.2 CO 3 , Na 2 CO 3 , and K 2 CO 3 When element X is Ca or Mg, the compound containing element X is CaCO 3 and MgCO 3 When element X is P, B, Al, or La, the compounds containing element X are 2 O 5 , B 2 O 3 , Al 2 O 3 , and La 2 O 3 was used.

[0097] The amount of the compound containing element X was adjusted so that the content of element X in the negative electrode material obtained in the third step would be the value shown in Table 1. The content of element X in the negative electrode material in Table 1 indicates the mass ratio to the total amount of elements other than oxygen.

[0098] [Second process] A silicate containing element X was mixed with raw material silicon (3N, average particle size 10 μm). In the mixture, the mass ratio of silicate to raw material silicon was 40:60.

[0099] The mixture was loaded into a pot (made of stainless steel, volume: 500 mL) of a planetary ball mill (manufactured by Fritsch, P-5), 24 stainless steel balls (diameter 20 mm) were placed in the pot, the lid was closed, and the mixture was ground at 200 rpm for 50 hours in an inert atmosphere.

[0100] Next, the powder mixture was taken out in an inert atmosphere, and sintered at 600°C for 4 hours in an inert atmosphere while applying pressure from a hot press machine to obtain a sintered body (composite intermediate) of the mixture. The obtained composite intermediate was pulverized and passed through a 40 μm mesh to obtain composite intermediate particles.

[0101] [3rd step] In Examples 1 to 4 and Comparative Examples 2 to 5, the particles of the composite intermediate were subjected to a predetermined heat treatment in an inert atmosphere to remove La dispersed in the particles of the composite intermediate. 2 S 2 O 7 The crystallinity of the composite material particles was increased to obtain composite material particles having an average particle size of 5 μm, which were then sieved to obtain negative electrode materials a1 to a4 and b2 to b5.

[0102] In Comparative Example 1, the composite intermediate particles were not subjected to the above-mentioned heat treatment (third step), but were sieved to obtain composite intermediate particles having an average particle size of 5 μm, which were used as negative electrode material b1.

[0103] [Analysis of negative electrode materials] For all negative electrode materials, the crystallite size of the silicon particles in the composite material determined by the method described above was 15 nm. For example, for negative electrode material a1, the silicon content in the composite material (the total of silicon contained in the silicon particles and the silicate phase) determined by the method described above was 93.3 mass%.

[0104] For the negative electrode materials a1 to a4, X-ray diffraction and electron diffraction measurements revealed that La 2 S 2 O 7 It was confirmed that the crystal phase of the above was formed. In the negative electrode materials a1 to a4, diffraction peaks were confirmed near the diffraction angles 2θ=26°, 27°, 28°, and 33° in the X-ray diffraction patterns (hereinafter referred to as XRD patterns) obtained by X-ray diffraction measurement using Cu-Kα radiation. The half-width of the diffraction peak near the diffraction angle 2θ=33° was 0.75° or less. In addition, the interplanar spacings calculated based on the data of the diffraction points obtained by the electron beam diffraction measurement were 2.6 Å to 2.75 Å, 3.6 Å to 3.7 Å, 5.2 Å to 5.3 Å, and 7.3 Å to 7.4 Å.

[0105] The SEM images (backscattered electron images) of the cross sections of the negative electrode materials a1 to a4 show that La is present in the matrix of the silicate phase. 2 S 2 O 7 It was confirmed that the crystalline phase of La was dispersed.2 S 2 O 7 The equivalent circle diameter of the crystal phase was in the range of 10 nm to 1.0 μm.

[0106] In the negative electrode materials a1 to a4, La was observed around the diffraction angles 2θ = 33° and 29° in the XRD patterns, respectively. 2 S 2 O 7 The first diffraction peak attributed to silicon particles and the second diffraction peak attributed to silicon particles were confirmed. The ratio of the intensity I1 of the first diffraction peak to the intensity I2 of the second diffraction peak: I1 / I2, was 0.25 or less.

[0107] In the negative electrode material b1, La was observed at diffraction angles 2θ = 26°, 27°, 28°, and 33° in the XRD pattern. 2 S 2 O 7 However, in the case of the negative electrode material b1, the half-width of the diffraction peak at the diffraction angle 2θ = 33° was as large as 1.0°, and the diffraction peak was not attributed to La. 2 S 2 O 7 It was confirmed that the crystallinity of the phase was low.

[0108] In the negative electrode materials b2 to b5, La 2 S 2 O 7 No diffraction peaks attributable to were observed.

[0109] [Preparation of negative electrode] The negative electrode material and graphite were mixed in a mass ratio of 5:95 and used as the negative electrode active material. The negative electrode active material, sodium carboxymethylcellulose (CMC-Na), and styrene-butadiene rubber (SBR) were mixed in a mass ratio of 97.5:1:1.5, water was added, and the mixture was stirred using a mixer (TK Hivismix, manufactured by Primix Corporation) to prepare a negative electrode slurry. Next, 1 m of the mixture was applied to the surface of the copper foil. 2 The negative electrode slurry was applied so that the mass of the negative electrode mixture per sheet was 190 g, the coating was dried, and then rolled to form a copper foil with a density of 1.5 g / cm on both sides. 3Thus, a negative electrode having a negative electrode mixture layer of the above formula was fabricated.

[0110] [Preparation of positive electrode] Lithium cobalt oxide, acetylene black, and polyvinylidene fluoride were mixed in a mass ratio of 95:2.5:2.5, N-methyl-2-pyrrolidone (NMP) was added, and the mixture was stirred using a mixer (TK Hivismix, manufactured by Primix Corporation) to prepare a positive electrode slurry. The positive electrode slurry was then applied to the surface of an aluminum foil, the coating was dried, and the mixture was rolled to form a positive electrode slurry having a density of 3.6 g / cm on both sides of the aluminum foil. 3 A positive electrode having a positive electrode mixture layer of the above formula was fabricated.

[0111] [Preparation of non-aqueous electrolyte] LiPF was dissolved in a mixed solvent containing ethylene carbonate (EC) and diethyl carbonate (DEC) in a volume ratio of 3:7. 6 was dissolved at a concentration of 1.0 mol / L to prepare a non-aqueous electrolyte.

[0112] [Preparation of non-aqueous electrolyte secondary battery] A tab was attached to each electrode, and the positive and negative electrodes were spirally wound with a separator between them so that the tabs were located at the outermost periphery to prepare an electrode group. The electrode group was inserted into an exterior body made of an aluminum laminate film and vacuum dried at 105°C for 2 hours. After that, a nonaqueous electrolyte was injected and the opening of the exterior body was sealed to obtain a battery.

[0113] In the above-mentioned production of the negative electrode, negative electrode materials a1 to a4 and b1 to b5 were used to obtain batteries A1 to A4 of Examples 1 to 4 and batteries B1 to B5 of Comparative Examples 1 to 5. The following cycle test was carried out on each of the obtained batteries.

[0114] [Cycle test] <Charging> The battery was charged at a constant current of 1 It (800 mA) until the voltage reached 4.2 V, and then charged at a constant voltage of 4.2 V until the current reached 1 / 20 It (40 mA).

[0115] <Discharge> A constant current discharge was performed at a current of 1 It (800 mA) until the voltage reached 2.75 V.

[0116] The rest period between charging and discharging was 10 minutes. The charging and discharging were performed at 25°C.

[0117] For each battery, the ratio of the discharge capacity at the first cycle to the charge capacity at the first cycle was calculated as the initial charge / discharge efficiency. The initial charge / discharge efficiency was expressed as a relative value, with the initial charge / discharge efficiency value obtained for Battery B1 of Comparative Example 1 taken as 100.

[0118] For each battery, the ratio of the discharge capacity at the 100th cycle to the discharge capacity at the 1st cycle was calculated as the cycle capacity retention rate. The cycle capacity retention rate was expressed as a relative value, with the cycle capacity retention rate obtained for battery B1 in Comparative Example 1 taken as 100.

[0119] The evaluation results are shown in Table 1.

[0120] [Table 1]

[0121] High initial charge / discharge efficiency was obtained in the batteries A1 to A4 of Examples 1 to 4, compared with the batteries B1 to B5 of Comparative Examples 1 to 5. The batteries A1 to A4 also achieved high cycle capacity retention rates.

[0122] In battery B1, La dispersed in the silicate phase 2 S 2 O 7 The initial charge-discharge efficiency was low due to the low crystallinity of La 2 S 2 O 7 In the batteries B2 to B5 using the negative electrode materials b2 to b5 not containing this crystalline phase, the initial charge-discharge efficiency decreased. [Industrial Applicability]

[0123] The nonaqueous electrolyte secondary battery according to the present invention is useful as a main power source for mobile communication devices, portable electronic devices, and the like. [Explanation of symbols]

[0124] 1 electrode group 2 Positive Lead 3 Negative lead 4 Battery case 5 Sealing plate 6 Negative terminal 7 Gasket 8. Sealing 11 Composite materials 12. Silicate phase of element E1 13 Silicon particles 14 Crystalline phases of rare earth silicates 15 Conductive layer

Claims

1. A silicate phase, silicon particles dispersed within the silicate phase, and a crystalline phase dispersed within the silicate phase, The silicate phase contains at least one element E1 selected from the group consisting of alkali metal elements and Group 2 elements, the crystalline phase comprises a rare earth element, silicon, and oxygen; The crystalline phase contains a compound A represented by the general formula: M 2 Si 2 O 7 , M is the rare earth element.

2. 2 . The negative electrode material for a nonaqueous electrolyte secondary battery according to claim 1 , wherein the content of the rare earth element is 0.2 mass % or more and 21 mass % or less with respect to the total amount of elements other than oxygen.

3. 3. The negative electrode material for a non-aqueous electrolyte secondary battery according to claim 1, wherein the rare earth element comprises at least one selected from the group consisting of lanthanum, cerium, praseodymium, and neodymium.

4. The negative electrode material for a nonaqueous electrolyte secondary battery according to any one of claims 1 to 3, wherein an X-ray diffraction pattern obtained by X-ray diffraction measurement using Cu-Kα radiation has diffraction peaks attributable to the compound A at diffraction angles 2θ of approximately 26°, 27°, 28°, and 33°.

5. The X-ray diffraction pattern obtained by X-ray diffraction measurement using Cu-Kα radiation has a first diffraction peak attributable to the compound A and a second diffraction peak attributable to the silicon particles at diffraction angles 2θ=33° and 29°, respectively.

4. The negative electrode material for a nonaqueous electrolyte secondary battery according to claim 1, wherein a ratio I1 / I2 of an intensity I1 of the first diffraction peak to an intensity I2 of the second diffraction peak is 0.25 or less.

6. 4. The negative electrode material for a non-aqueous electrolyte secondary battery according to claim 1, wherein the crystal structure of the crystal phase includes at least one selected from the group consisting of monoclinic, tetragonal and triclinic.

7. 4. The negative electrode material for a non-aqueous electrolyte secondary battery according to claim 1, wherein the crystalline phase has a lattice spacing of at least 2.6 Å to 2.75 Å, 3.6 Å to 3.7 Å, 5.2 Å to 5.3 Å, and 7.3 Å to 7.4 Å.

8. The negative electrode material for a non-aqueous electrolyte secondary battery according to any one of claims 1 to 7, wherein the element E1 includes at least one selected from the group consisting of lithium, sodium, potassium, magnesium, calcium, and barium.

9. The silicate phase further comprises element E2, The negative electrode material for a nonaqueous electrolyte secondary battery according to any one of claims 1 to 8, wherein the element E2 includes at least one selected from the group consisting of zirconium, niobium, tantalum, vanadium, titanium, phosphorus, bismuth, zinc, tin, lead, antimony, cobalt, fluorine, tungsten, aluminum, and boron.

10. A positive electrode, a negative electrode, and a non-aqueous electrolyte, The negative electrode of a non-aqueous electrolyte secondary battery comprises the negative electrode material according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Conductive material for oxygen ion and its production

    JP1996208333A

  • Nonaqueous electrolyte battery and negative active material

    JP2007059213A

  • Secondary battery and negative electrode active material

    JP2014199753A

  • Composite particle for nonaqueous electrolyte secondary battery

    JP2014220216A

  • Solid oxide fuel cell system

    JP2015069753A